Integrating E-Module with Project Based Learning (PjBL): a Strategy to Improve Students' Collaboration Abilities and Scientific Literacy - Umi Nurussalamah; Siska Desy Fatmaryanti; Sriyono (Postgraduate, University of Mataram, 2025)
This study explores the integration of E-Modules with Project-Based Learning (PjBL) as a strategy to enhance student collaboration and scientific literacy. The research follows the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) model and was conducted in one of the high schools in Central Java, involving limited trials and extensive trials (5 and 31) students. The developed E-Module was validated by experts, achieving an average score of 3.50 in both material and media evaluation, categorizing it as valid. The practicality assessment of the E-Module obtained 84.47% with a very practical category. Observations of collaboration skills yielded an 80.5% practicality score. The module's effectiveness was evident in the significant improvement of students' collaboration skills (N-Gain = 0.8, high category) and scientific literacy (N-Gain = 0.74, high category). These findings highlight the potential of PjBL-based E-Modules as an effective tool for improving student engagement, collaboration, and scientific literacy in measurement-related learning. The results suggest that this approach can be replicated or expanded to other topics to further enhance student-centered learning.